Como brincam as crianças da comunidade quilombola de Jamary dos Pretos em Turiaçu - Ma - GOMES, Nayra Rejane Rolim (2018)
The Brazilian population is made up of a diverse people with inheritance from Europeans, Indians and Africans. Thus, a large group of traditional communities such as the Quilombolas are part of our society. Human behavior is dependent on the social context and customs of each people, and among these behaviors stands out the play, which is full of meaning and expressions of the customs that surround each child. Objective: To understand how children of the Quilombola community of Jamary of the blacks in Turiaçu – MA, through the description of the play and the identification of the customs of the community researched. Methods: Ethnographic qualitative research was accomplished through observation and coexistence in the Quilombola community and the interstructured interviews. For analysis, the method of analysis of content using quantitative and qualitative criteria was used. Results: Were catalogued 33 pranks in Jamary of the blacks and perceived that although many children report not playing with parents, historical elements of Jamary and customs related to day-to-day in the community are perceived during the play. Common jokes in the researched community are found also in other regions, according to other authors, but each site carries peculiar elements of their societies. Direct contact with nature also brings meaning to the toys found. Conclusion: Jamary's children's favorite game of the Blacks was soccer, having as their favorite toy the doll. They like to play at home, in contact with nature and animals. They report not playing with parents, but they learn to play games with other friends and often with parents or older people in the community. In the form of text, clippings of speeches, images and reflections, it was possible to transcribe the plays of Jamary's children from the Blacks and how what is learned and observed on a daily basis is so naturally demonstrated by these individuals. The customs of Jamary are impregnated in the form of play and the history of Jamary continues to be constructed through the children.